Bacteria associated with Parthenium hysterophorus root exudate influence olfactory oviposition responses of Anopheles gambiae - Milugo, Trizah K.; Torto, Baldwyn; Tchouassi, David P. (Frontiers in Tropical Diseases, 2024)
IntroductionPreviously, we documented that the malaria vector Anopheles gambiae responds to volatile emissions from the root exudate water of the invasive plant, Parthenium hysterophorus. However, the origin of the volatiles remains to be investigated. Here, we isolated bacteria from the root exudate water of the plant, test the influence of their volatiles in gravid An. gambiae oviposition, and examined relationships between volatile profiles and oviposition.MethodsBacteria from root exudate water of P. hysterophorus were isolated using culture on Luria Bertani medium and identified by sequencing the 16S rRNA gene. Cultures of individual isolates were evaluated for egg laying response by gravid An. gambiae and number of eggs laid compared using generalized linear models relative to those in crude bacteria-mixture. Headspace volatile emissions of the bacterial isolates were analyzed by gas chromatography coupled to mass spectrometry (GC-MS) and relationships between volatile organic compound (VOC) profiles and gravid mosquito oviposition examined using Random Forest Analysis. Proximate analysis was performed to assess the difference in volatile chemistry among the different isolates.ResultsThree isolates were identified as Gram-negative bacteria belonging to two families: Enterobacteriaceae (Enterobacter sp. and Enterobacter mori) and Alcaligenaceae (Alcaligens aquatilis). An. gambiae laid 3-fold more eggs in cultures of A. aquatilis than in those of Enterobacter sp. In turn, approx. 4-fold more eggs were laid in cultures of E. mori than A. aquatilis. Overall, 16 VOCs were identified in the headspace of the isolates belonging to the chemical classes benzenoids, pyrazines, aldehydes, terpenes, alcohols, alkanes, and indoles. Random Forest Analysis identified 10 compounds contributing the most to the attraction of odors of the bacteria isolates to oviposition. Specifically, dodecane and indole were emitted in higher amounts in odors of Enterobacter sp than the other two species. Proximate analysis revealed differential attraction of the isolates on the gravid mosquito to be associated with their volatile profiles.ConclusionOur results provide first report of E. mori or A. aquatilis mediating attractive oviposition responses in An. gambiae in support of the important role microbes play in insect oviposition. The potential use of the microbes and associated volatiles in malaria vector management needs further investigation.